2011
DOI: 10.1364/ol.36.001332
|View full text |Cite
|
Sign up to set email alerts
|

Achromatization of Wollaston polarizing beam splitters

Abstract: We describe the achromatization of Wollaston prisms to reduce the angular dispersion in the splitting angle. Analytical theory and ray-tracing modeling is presented. In an example application, a sixfold reduction in dispersion is achieved for wavelengths in the region 400 nm to 1.7 μm. Experimental proof of concept is demonstrated, and in an example application, the spectral dispersion of extended images recorded through cascaded Wollaston prisms is shown to be reduced by an order of magnitude.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The effect was manifestly negligible over the approximately 50 nm bandwidth used in this work. Recently, Wong et al 47 demonstrated experimentally the achromatization of a Wollaston prism with the use of a compensating prism. An achromatic Wollaston prism assembly of this type may enable single-exposure OBM with a white light source.…”
Section: Discussionmentioning
confidence: 99%
“…The effect was manifestly negligible over the approximately 50 nm bandwidth used in this work. Recently, Wong et al 47 demonstrated experimentally the achromatization of a Wollaston prism with the use of a compensating prism. An achromatic Wollaston prism assembly of this type may enable single-exposure OBM with a white light source.…”
Section: Discussionmentioning
confidence: 99%
“…With a 1D (or linearly variable filter) data is recorded on sequential frames leading to spectral latency, however, this can be reduced by optimising the design according equation (3). Spectral latency can be eliminated using a 2D colour filter or mask.…”
Section: Discussionmentioning
confidence: 99%
“…The optical system is a simplified version of a previously reported system based on image replication [2,3]. In this simplified version, a pair of polarising beamsplitters is used to split an image into two identical sub-images of orthogonal polarisation that are simultaneously projected onto a focal plane array (FPA).…”
Section: Design and Principle Of Operationmentioning
confidence: 99%
“…As is well known, the conventional polarization beam splitters used in free-space optical signal processing are generally bulk-type ones by utilizing prism structures [1], [2], which employ natural birefringence of the anisotropic materials. Although the polarization splitting function can be easily realized in optical system, its major drawback is usually cumbersome.…”
Section: Introductionmentioning
confidence: 99%